Modulation of Hippocampal GABAergic Neurotransmission and Gephyrin Levels by Dihydromyricetin Improves Anxiety - Silva, Joshua; Shao, Amy S.; Shen, Yi; Davies, Daryl L.; Olsen, Richard W.; Holschneider, Daniel P.; Shao, Xuesi M.; Liang, Jing (Frontiers in Pharmacology, 2020)
Anxiety disorders are the most common mental illness in the U.S. and are estimated to consume one-third of the country’s mental health spending. Although anxiolytic therapies are available, many patients exhibit treatment-resistance, relapse, or substantial side effects. An urgent need exists to explore the underlying mechanisms of chronic anxiety and to develop alternative therapies. Presently, we identified dihydromyricetin (DHM), a flavonoid that has anxiolytic properties in a mouse model of isolation-induced anxiety. Socially isolated mice demonstrated increased anxiety levels and reduced exploratory behavior measured by elevated plus-maze and open-field tests. Socially isolated mice showed impaired GABAergic neurotransmission, including reduction in GABAA receptor-mediated extrasynaptic tonic currents, as well as amplitude and frequency of miniature inhibitory postsynaptic currents measured by whole-cell patch-clamp recordings from hippocampal slices. Furthermore, intracellular ATP levels and gephyrin expression decreased in anxious animals. DHM treatment restored ATP and gephyrin expression, GABAergic transmission and synaptic function, as well as decreased anxiety-like behavior. Our findings indicate broader roles for DHM in anxiolysis, GABAergic neurotransmission, synaptic function. Collectively, our data suggest that reduction in intracellular ATP and gephyrin contribute to the development of anxiety, and represent novel treatment targets. DHM is a potential candidate for pharmacotherapy for anxiety disorders.